COGNITIVE IMPAIRMENT OCCURS BEFORE LOSS OF FUNCTION IN ALS. Issue 12 (15th November 2016) - Gabel, Matt; Tsermentseli, Stella; Goldstein, Laura H; Al-Chalabi, Ammar; Young, Alexandra; Alexander, Daniel; Leigh, P. Nigel; Cercignani, Mara
Abstract : Objectives: Using a historical amyotrophic lateral sclerosis (ALS) dataset comprising detailed cognitive and clinical assessments, we used a novel event-based model to analyse the likely ordering of these biomarkers in the progression of ALS. Methods: The dataset was derived from a cross-sectional sample of 28 ALS patients who were not classified as having ALS-FTD and 26 matched controls (see1 regarding cognitive and clinical assessments). The event-based model was adapted for ALS from previous work in Alzheimer's disease.2 3 Unlike traditional models of disease progression, event-based models do not rely on a priori staging of patients but extract the event ordering directly from the data, thus minimising subjective bias. Results: The most likely order of progression showed that changes in executive function occur at an early stage of disease evolution. Language impairment tended to occur after executive dysfunction. Changes in functional ability assessed by rate of change of ALSFRS-R occurred after the changes in executive function. Conclusions: These findings suggest that executive dysfunction occurs early in the evolution of ALS.